Implementasi Internet of Things Pada Sistem Monitoring Suhu dan Kelembaban Pada Ruangan Pengering Berbasis Web - Fauziah Y.Q. Ontowirjo; Vecky C. Poekoel; Pinrolinvic D.K. Manembu; Reynold F. Robot (Universitas Sam Ratulangi, 2018)
Abstract — The temperature and humidity monitoring system in the drying room is one of the technologies that are being developed and very necessary for agricultural purposes in Indonesia. The results of the study according to the Red Onion Postharvest Handling Technology in Indonesia that in order to produce good tuber quality, the recommended temperature is around 26-29°C with humidity value from 70-80% (in hybrid dryer room). To monitor the temperature and humidity in the drying room is very ineffective if we do it manually especially on the long distance, therefore a system that can be used to monitor temperature and humidity in the drying room based on website uses Internet of Things facilities where the system monitors the temperature and humidity condition in the drying room in realtime. Temperature and humidity data in this drying room are saved in the database. This system is made using raspberry pi 3 B + model as a microprocessor, temperature and humidity sensor to detect temperature and humidity in the drying room, and the Logitech c270 webcam to monitor the drying room which acts as a CCTV to maintain security in the location of the drying room.Keywords — Internet of Things; Monitoring System; Raspberry Pi; Temperature and humidity sensor; Website database Abstrak — Sistem monitoring suhu dan kelembaban pada ruangan pengering merupakan salah satu teknologi yang sedang dikembangkan dan sangat diperlukan untuk kepentingan pertanian di Indonesia. Hasil penelitian menurut Teknologi Penanganan Pascapanen Bawang Merah di Indonesia bahwa untuk menghasilkan kualitas umbi yang baik maka suhu yang direkomendasikan sekitar 26 - 29°C dengan nilai kelembaban berkisaran 70 - 80% (Dalam ruangan pengering hybrid). Untuk memonitoring suhu dan kelembaban pada ruangan pengering sangatlah tidak efektif jika dilakukan secara manual terlebih jika berada dari jarak jauh, maka dari itu dibuatlah sebuah sistem yang bisa digunakan untuk memonitoring suhu dan kelembaban pada ruangan pengering berbasis website menggunakan fasilitas Internet of Things dimana sistem ini memonitoring keadaan suhu dan kelembaban pada ruangan pengering dalam waktu nyata. Data suhu dan kelembaban pada ruangan pengering ini disimpan pada database. Sistem ini dibuat menggunakan raspberry pi 3 model B+ sebagai mikroprosesor, sensor suhu dan kelembaban untuk mendeteksi suhu dan kelembaban pada ruangan pengering, serta webcam Logitech c270 untuk memonitor keadaan ruangan pengering yang bertindak sebagai CCTV untuk menjaga keamanan pada lokasi ruangan pengering.Kata kunci — Database website; Internet of Things; Raspberry Pi; Sensor Suhu dan Kelembaban; Sistem Monitoring